STRATEGI KOMUNIKASI PEMBELAJARAN DARING MASA COVID-19 DI MAN INSAN CENDEKIA KABUPATEN HALMAHERA BARAT - Din, Makbul AH; Nurjaman, Enang Yusuf (Jurnal Common, 2022)
This study intends to explore the online learning communication strategy carried out by the Madrasah Aliyah Negeri Insan Cendekia (MAN IC) West Halmahera, North Maluku Province during the Covid 19 period, so that learning is carried out in accordance with the targets and the results achieved are in accordance with face-to-face learning. This study uses a descriptive qualitative approach with phenomenological theory to dig deeper into the phenomenon of online learning and the intersubjective relationships between teachers, students and policy makers, namely school principals. Data collection techniques in this study were participatory observation, in-depth interviews and documentation studies. The results of the strategy research conducted by Madrasah Aliyah Negeri Insan Cendekia (MAN IC) West Halmahera Maluku Province are online learning using synchronous e-learning, the Multiflatform Learning Management System and with full-time service teachers from all teachers, with this strategy the quality of learning goes according to the targets set by the school.